God’s intermediaries: a study into chaplains’ information behaviour - Robson, Kieran; Ruthven, Ian; Innocenti, Perla (Information Research an international electronic journal, 2024)
Introduction. This study investigates the information behaviours that chaplains across the UK and Ireland use in their day-to-day work when interacting with vulnerable people. Methods. Eight chaplains working with vulnerable people were interviewed using semi-structured interviews. The interviews aimed to find out how chaplains acted as intermediaries and what other information behaviour techniques they use in their work. Analysis. Thematic analysis was used to analyse the transcribed interviews, the four main themes of information work, work duties, ways of working and faith were discovered. Findings. A range of information behaviours were found to be used by chaplains when interacting with their clients. These information behaviours included information chunking, avoidance and acting as an information intermediary. Conclusion. This paper shows the range of information behaviours that chaplains utilise when working with vulnerable communities.